THE INFLUENCE OF ONLINE CUSTOMER REVIEW AND ONLINE CUSTOMER RATING ON PURCHASE DECISIONS AT TOKOPEDIA (CASE STUDY OF TOKOPEDIA USERS IN MEDAN DISTRICT, JOHOR) - Arif Muluk Rahman; Wan Rizca Amelia; Fadli Adnin Nasution; Zulham Zulham (Universitas Dharmawangsa Medan, 2022)
ABSTRACTThis study intends to examine how online customer reviews and ratings affect purchase choices. Purposive sampling is used in this form of study to choose the sample, which might include as many as 96 Tokopedia customers who have made purchases there. It is associated with a quantitative approach. Primary data are the kind used. The information utilized was derived from the responses provided by the respondents to the questionnaires that were given out. Utilizing the SPSS 25 for Windows application, validity testing, reliability testing, traditional assumption testing, and hypothesis testing are the data analysis methodologies performed. The study's findings show that online customer reviews (X1) and online customer ratings (X2) have a substantial impact on purchase decisions (Y) at Tokopedia.Keywords: Online Customer Review, Online Customer Rating and Purchase Decision.